Mating density and the strength of sexual selection against deleterious alleles in Drosophila melanogaster. - Sharp, N.P.; Agrawal, A.F. (Evolution, 2008)
Deleterious alleles constantly enter populations via mutation. Their presence reduces mean fitness and may threaten population persistence. It has been suggested that sexual selection may be an efficient way by which deleterious alleles are removed from populations but there is little direct experimental evidence. Because of its potential role in mutational meltdowns, there is particular interest in whether the strength of sexual selection changes with density. For each of eight visible markers in Drosophila melanogaster we have compared the strength of sexual selection at two densities. We find evidence of strong sexual selection against most but not all of these alleles. There is no evidence that sexual selection tends to be stronger (or weaker) at high density relative to low density. In addition, we also measure the effects of these mutations on two key parameters relevant to population productivity--juvenile viability and female fecundity. In most cases, sexual selection is as strong or stronger than these other forms of selection.